2020
DOI: 10.3389/fphy.2020.591995
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Stability of the Peregrine and Related Breathers

Abstract: In this note, we review stability properties in energy spaces of three important nonlinear Schrödinger breathers: Peregrine, Kuznetsov-Ma, and Akhmediev. More precisely, we show that these breathers are unstable according to a standard definition of stability. Suitable Lyapunov functionals are described, as well as their underlying spectral properties. As an immediate consequence of the first variation of these functionals, we also present the corresponding nonlinear ODEs fulfilled by these nonlinear Schröding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Here, the nonlinear dynamics interfering in the modulation process may violate this demand. In fact, an absolute spatial MI regime causes the breather and rogue waves breeding thus, an irreversible instability [49][50][51][52][53][54][55]. In this connection, spatial amplitude profile is simulated in the proposed Mach-Zehnder modulator as shown in Fig.…”
Section: B Spatial MI and Breathermentioning
confidence: 99%
“…Here, the nonlinear dynamics interfering in the modulation process may violate this demand. In fact, an absolute spatial MI regime causes the breather and rogue waves breeding thus, an irreversible instability [49][50][51][52][53][54][55]. In this connection, spatial amplitude profile is simulated in the proposed Mach-Zehnder modulator as shown in Fig.…”
Section: B Spatial MI and Breathermentioning
confidence: 99%
“…In particular, for a fixed t > 0 and as z → ∞, they claim that (1.5) log P(D(t, z)) = −I(ϑ * (z)) + o (1).…”
Section: I(ϑ)mentioning
confidence: 99%
“…In the case µ = −1, some solutions to (1.1) blow up in finite time, and therefore they cannot be extended indefinitely, see for example [51,35]. In contrast to this generic behavior, certain types of initial data give rise to traveling waves and soliton solutions, see [1] and the references therein. These solutions display an unusual long-term behavior, and as a result they are considered rare phenomena.…”
mentioning
confidence: 99%
“…Perturbations to the AB were considered in the periodic space H s per for s > 1/2. Similar techniques were applied to KMB and PRW in [4] (see also the review in [5]). It was shown that both KMB and PRW are unstable with respect to perturbations in H s (R) for s > 1/2.…”
Section: Introductionmentioning
confidence: 99%